Plasma-chemical method of grain fungal contamination control - Taran, G.V.; Pugach, S.G.; Zamuriev, A.A.; Opalev, P.O.; Yaroshenko, M.O. (Вопросы атомной науки и техники, 2020)
The experimental results n the effect of grain treatment with ozone-air mixture on the level of artificial grain contamination with micromycetes are presented. The contamination dynamics for 1000 kg of wheat grain contaminated with Penicillium nordicum and Aspergillus flavus and stored in the prototype grain storage unit in ozone environment for 6 months is shown. The study on the effect of ozone on the growth inhibition of Aspergillus flavus or maize grain and Penicillium verrucosum for wheat grain in a 100 dm³ silo is presented. The effect of ozone on the content of aflatoxins in maize grain additionally contaminated with Aspergillus flavus is studied. The efficiency of ozone technologies for large-scale grain storage, as well as for reducing fungal contamination and controlling mycotoxin content in food grains, is shown.